The onset of double-diffusive convection in a nanofluid saturated porous layer: Cross-diffusion effects; European Journal of Mechanics - B/Fluids; Vol. 65 - Umavathi J. C. Jawali; Sheremet M. A. Mikhail Aleksandrovich; Ojjela O. Odelu; Reddy G. J. Janardhan (2017, 2017)
Title screen